Analysis of the New Zealand agricultural phosphorus budget : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science, Agricultural Science at Massey University, Manawatū, Palmerston North, New Zealand - de Klerk, Theane (Massey University, 2025)
The New Zealand agricultural industry utilises a significant amount of phosphorus (P) in the form of fertiliser to support sustainable and economically viable agricultural production, in particular, to support pasture and crop growth for the pastoral farming sectors. Phosphorus can however have significant negative environmental effects, meaning that sustainable management of P resources are required to reduce the risk of eutrophication of freshwater bodies. … This study represents the most comprehensive analysis of P maintenance requirements across New Zealand agriculture and for the first time, presents a national agricultural P balance for the country. This information is critical to not only ensure best practice P fertiliser use within New Zealand, but to allow us to benchmark both our industry and national scale P balances internationally. These insights are useful to project future trends in P fertiliser requirements, highlighting industries and regions which may require higher inputs of P to maintain economic productivity.
Figures 2.1 & 2.3 are reproduced with permission.
Keywords: 300411 Fertilisers (incl. application)